Re-imaging Nigeria value of safety through the discourse of security situations among community leaders in Akinyele Local Government Area of Oyo State (2022)
Insecurity in Nigeria has turned out to be a phenomenon which goes beyond insurgency, organised kidnapping and other socio-economic and political tensions. The aim of the study is to assess Nigeria value of safety through a critical discourse of some security Situation among community leaders in Akinyele local government area of Oyo state. The study adopted the qualitative research approach. The participants of the study comprised of 18 stakeholders holding key community leadership positions in Akinyele local government area of the state. The participants were selected using the intense-case of purposive sampling technique. Data were collected through audio-taped group interview. The credibility of this study was enhanced by expert review. The interview schedule reviewed by experts and the reliability was established using the formula proposed by Miles and Huberman which yielded 0.74. The data collected from the interview were examined using thematic analysis. The findings of the study showed that safety value is of paramount importance and should be inculcated in people at the early stage of life. The participants affirmed that community members are critical to upholding value of safety even when there are security apparatus such as Amotekun, Vigilante group within the axis. Thus, participants suggested that community fora should organise talks on good value acquisition as fundamental for safe living. Hence, it is recommended that security education should be allowed to thrive as course independent of any discipline and must be made compulsory in the school System and at all levels of education. There is need to adopt learner-centred methods to disseminate core values and tenet of security to students. Efforts should be geared towards making Nigeria a secured society through adult modeling of positive behaviours and exhibition of good conducts.